Implementation of multicultural value education at aliyah madrasah on lombok island - Partono; Ashif Az Zafi; Moh. Amirudin (At Turots: Jurnal Pendidikan Islam, 2025)
This research aims to explore the implementation of multicultural value education in madrasas on the island of Lombok, with a focus on Madrasah Aliyah (MAS) Ishlahul Ikhwan NW Mispalah Lombok. The main problem in this study is how to apply multicultural values in madrasas and the results obtained. This study uses a qualitative approach with a case study method to analyze how the madrasah integrates multicultural values in the curriculum, as well as the implementation of activities that support multicultural education. The results of the study show that this madrasah has succeeded in instilling multicultural values through several strategies, including: integrating multicultural values in the curriculum, implementing cross-cultural activities, tolerance and empathy education, the use of learning media that reflects diversity, and the development of a school environment that supports diversity. Through this approach, it is hoped that a generation can be created that has an attitude of tolerance, mutual respect, and care for cultural diversity in society.